High-Performance Aqueous Zinc-Ion Batteries Realized by MOF Materials - Pu, Xuechao; Jiang, Baozheng; Wang, Xianli; Liu, Wenbao; Dong, Liubing; Kang, Feiyu; Xu, Chengjun (Nano-Micro Letters, 2020)
Rechargeable aqueous zinc-ion batteries (ZIBs) have been gaining increasing interest for large-scale energy storage applications due to their high safety, good rate capability, and low cost. However, the further development of ZIBs is impeded by two main challenges: Currently reported cathode materials usually suffer from rapid capacity fading or high toxicity, and meanwhile, unstable zinc stripping/plating on Zn anode seriously shortens the cycling life of ZIBs. In this paper, metal–organic framework (MOF) materials are proposed to simultaneously address these issues and realize high-performance ZIBs with Mn(BTC) MOF cathodes and ZIF-8-coated Zn (ZIF-8@Zn) anodes. Various MOF materials were synthesized, and Mn(BTC) MOF was found to exhibit the best Zn2+-storage ability with a capacity of 112 mAh g−1. Zn2+ storage mechanism of the Mn(BTC) was carefully studied. Besides, ZIF-8@Zn anodes were prepared by coating ZIF-8 MOF material on Zn foils. Unique porous structure of the ZIF-8 coating guided uniform Zn stripping/plating on the surface of Zn anodes. As a result, the ZIF-8@Zn anodes exhibited stable Zn stripping/plating behaviors, with 8 times longer cycle life than bare Zn foils. Based on the above, high-performance aqueous ZIBs were constructed using the Mn(BTC) cathodes and the ZIF-8@Zn anodes, which displayed an excellent long-cycling stability without obvious capacity fading after 900 charge/discharge cycles. This work provides a new opportunity for high-performance energy storage system. Highlights: 1 Various MOF materials were synthesized and investigated as ZIB cathodes. 2 A long-term stable ZIF-8@Zn anode was proposed by coating ZIF-8 material on the surface of zinc foils. 3 High-performance aqueous ZIBs were constructed using the Mn(BTC) cathode and the ZIF-8@Zn anode.